ACCOUNT OF ELECTRODYNAMIC AFFECT OF SHORT-CIRCUIT CURRENTS WHILE DESIGNING FLEXIBLE CURRENT-CONDUCTING WIRES 6 – 10 KV OF ELECTRIC SUPPLY SYSTEMS - I. I. Sergey; Yu. V. Bladyko; E. G. Ponomarenko; B. D. Tsemekhman; L. A. Penko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows a vital importance of electrodynamic affect account in respect of relatively small short-circuit-currents on flexible current-conducting wires of electric supply systems at long short-circuit duration. Insufficient electrodynamic stability of flexible current-conducting wires of type design has been revealed. While using simplified and numerical methods for calculation of wire dynamics optimum parameters of flexible current-conducting wires have been determined.